Benjamin G. Kohl, The Records of the Venetian Senate on Disk, 1335-1400, CD-ROM, Italica Press, New York 1997-2000 - Azzara, Claudio (Reti Medievali Rivista, 2005)
Recensione a Benjamin G. Kohl, The Records of the Venetian Senate on Disk, 1335-1400, CD-ROM, Italica Press, New York 1997-2000 <http://www.italicapress.com/index166.html>